1981
DOI: 10.1029/gl008i006p00565
|View full text |Cite
|
Sign up to set email alerts
|

Permeability and frictional properties of San Andreas Fault Gouges

Abstract: The permeability of a San Andreas fault gouge is determined under confining pressures up to 220 bars; it decreases with pressure from 10 nanodarcy at 15 bars to 0.3 nanodarcy at 220 bars. These values are lower than the values determined by Morrow et al. (1981). Five different samples of fault gouge with significantly different grain‐size distributions were sheared between rock joints under confining pressures to determine the effects of grain size and constitution on the strength of the fault gouge. The stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…In addition, it would usually be expected that friction coefficient would be low for systems with high water content and vast amounts of work on faults have shown that clays lower friction coefficients (e.g. Morrow et al, 1981;Chu et al, 1981). However, no correlation is observed between friction coefficient and either clay content or porosity (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, it would usually be expected that friction coefficient would be low for systems with high water content and vast amounts of work on faults have shown that clays lower friction coefficients (e.g. Morrow et al, 1981;Chu et al, 1981). However, no correlation is observed between friction coefficient and either clay content or porosity (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…A number of experimental studies have noted that matrix permeability across muddy fault zones is severely reduced, reaching values as low as 0.3 nD at confining pressures of up to 200 MPa (e.g. Chu et al 1981;Morrow et al 1981Morrow et al , 1984Brown & Moore 1993). The permeability of some of these clay-rich gouges was noted to be influenced by grain size distribution, confining pressure and differential stress, but was not controlled by the finite strain accumulated during these experiments.…”
Section: Faults In Mudstones As Sealsmentioning
confidence: 84%
“…For accretionary wedges, observed pore fluid pressures range from about 67.5% to nearly 100% of the lithostatic pressure (Davis et al, 1983). Chu et al (1981) and Bird (1984) give values of 0.2-0.3 for the coefficient of friction for clays or clayey fault gouges. Shear stresses within clay-rich material at the base of an accretionary wedge, subjected to the observed range of pore fluid pressures, will range from 0% to about 10% of the lithostatic pressure (eqn.…”
Section: Discussionmentioning
confidence: 99%